Knowledge mapping of global trends in DNA damage repair-related breast cancer research: a bibliometric study - Huang, Yajing; Wei, Shumei; Hu, Kaimin; Xiang, Xueping (Frontiers in Oncology, 2025)
BackgroundBreast cancer remains one of the leading causes of cancer-related morbidity and mortality among women worldwide. Recent advancements in our understanding of DNA damage repair (DDR) mechanisms have shed light on their specific role in the pathogenesis, progression, treatment resistance, and prognosis of breast cancer. In this study, we conducted a bibliometric study to map the global trends in DDR-related breast cancer research.MethodologyA search of publications on DDR in breast cancer from 1990 to 2024 was conducted using the Web of Science Core Collection. A comprehensive bibliometric analysis of the data was performed using CiteSpace, VOSviewer, and Bibliometrix. Additionally, for clinical trial data, the databases ClinicalTrials.gov (https://www.clinicaltrials.gov) and the WHO International Clinical Trials Registry Platform (ICTRP) (https://trialsearch.who.int) were queried.ResultsThe results revealed a continuous and steady growth in the number of articles published in this area over the past three decades and showed that the USA had produced the highest number of publications in this field, while Harvard University had published the largest number of articles. Jonkers, Jos was found to be the most published author, with 39 documents. Analysis of the journals showed that Cancer Research ranked as the most published journal, while Nature was the most cited. Combined with the keyword co-occurrence analysis and co-citation analysis, it emerged that “Targeting the DNA repair defect as a therapeutic strategy”, published in Nature (IF = 64.8) in 2005, had accumulated 529 local citations, indicating that research topics have focused on treatment regimens. For clinical trials, 124 studies were initially sourced—108 from ClinicalTrials.gov and 16 from ICTRP. After repetitive and correlation-based screening, 43 trials specifically addressing 13 different DDR-related drugs in breast cancer were included.ConclusionOverall, this study provides valuable insights into the current research achievements, latest advancements, and emerging global trends in DNA damage repair-related breast cancer research. With sustained clinical focus, more high-quality investigations combining DDR inhibitors with other treatment modalities are needed.